Fractional iron solubility of atmospheric iron inputs to the Southern Ocean - Winton, Victoria; Bowie, A.; Edwards, R.; Keywood, M.; Townsend, A.; van der Merwe, P.; Bollhöfer, A. (2015)
© 2015 Elsevier B.V.. Deposition of iron (Fe) bearing aerosols to Fe deficient waters of the Southern Ocean may drive rapid changes in primary productivity, trophic structure and the biological uptake of carbon dioxide. The fractional solubility (i.e., the ratio of water leachable Fe to total Fe) of aerosol Fe is an important variable determining its availability for biological uptake, and is a function of both particle type and the experimental conditions used to leach the particles. There have been few studies of fractional Fe solubility over the Southern Ocean where the aerosol loading is the lowest in the world. To investigate Southern Ocean aerosol Fe solubility, the fractional solubility of Fe was determined in cryogenically archived Southern Ocean aerosols. Samples were collected at the Cape Grim Baseline Air Pollution Station (CGBAPS), Tasmania, Australia from February 1999 to April 2000. Fractions determined included water soluble Fe (<0.45µm), labile Fe (>0.45µm; acetic acid and hydroxylamine hydrochloride leachable Fe) and refractory Fe (>0.45µm; total digestion using nitric and hydrofluoric acids). Extremely low Fe mass concentrations were observed for baseline Southern Ocean air during the study period. An inverse hyperbolic relationship was observed between fractional Fe solubility (0.5 to 56%) and total Fe mass concentration (0.04 to 5.8ngm3; excluding an anomalously high sample). A peak of 4.6ngm3 of labile Fe occurred during May/June 1999 and was linked to atmospheric transport from South Western Australia over the Southern Ocean. Bioavailable Fe was estimated by summing the water soluble and labile Fe fractions, and this likely represents the upper bound of long range transport aerosol over the Southern Ocean. The results confirm previous reports of a range of fractional Fe solubility within all atmospheric particles measured and also suggest that a large fraction of the Fe from Australian mineral aerosols is labile and potentially bioavailable.